2013
DOI: 10.1111/aos.12030
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the retinal nerve fibre layer and reduced retinal function assessed by optical coherence tomography and full‐field electroretinography in patients exposed to vigabatrin medication

Abstract: ABSTRACT.Purpose: To investigate the clinical value of assessment of peripapillary retinal nerve fibre layer (RNFL) thickness with OCT in addition to the evaluation of retinal function measured by full-field electroretinography (ff-ERG) in patients with suspected vigabatrin (VGB)-attributed visual field defects. Methods: Visual fields from adult patients in our clinical follow-up program for VGB medication were analysed. Twelve patients with suspected VGB-attributed visual field defects were selected for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…VGB toxicity has a complex pathophysiology occurring as a result of accumulation of VGB in the retina and/or elevated levels of retinal GABA. In humans, changes to the electrooculogram, 32 cone and rod system, 32 , 33 and disruption on retinal nerve fiber layer 34 occur with VGB treatment. A change in the electrooculogram is probably an early, possibly reversible retinal defect attributed to VGB, resulting from disruption at the retinal pigment epithelium/photoreceptors border.…”
Section: Discussionmentioning
confidence: 99%
“…VGB toxicity has a complex pathophysiology occurring as a result of accumulation of VGB in the retina and/or elevated levels of retinal GABA. In humans, changes to the electrooculogram, 32 cone and rod system, 32 , 33 and disruption on retinal nerve fiber layer 34 occur with VGB treatment. A change in the electrooculogram is probably an early, possibly reversible retinal defect attributed to VGB, resulting from disruption at the retinal pigment epithelium/photoreceptors border.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of the retinal nerve fibre layer using optical coherence tomography has recently been introduced as an alternative method for follow‐up of vigabatrin toxicity . However, optical coherence tomography also requires the cooperation of the patient.…”
mentioning
confidence: 99%
“…8 Examination of the retinal nerve fibre layer using optical coherence tomography has recently been introduced as an alternative method for follow-up of vigabatrin toxicity. 9 However, optical coherence tomography also requires the cooperation of the patient. According to the guidelines, patients who are not subject to scheduled ophthalmic testing should not continue with vigabatrin treatment.…”
mentioning
confidence: 99%
“…It has been suggested that OCT be used to screen for VGB induced retinal toxicity because this test can show thinning of the RNFL which is associated with visual field loss [12]. Notably, here, the patient's OCT was normal until the acute presentation of decreased visual acuity (Figure 1, 2014.03).…”
Section: Discussionmentioning
confidence: 81%